The Utilization of The Microsoft Power Point and Microsoft Word Program in Physics Learning in Class X Students of Senior High School - Harnipa; Yusal, Yulianti (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2022)
This study aims to determine utilization of Microsoft Power point and Microsoft Word programs in learning physics in class X SMA Negeri 1 Ma’rang, Indonesia. This type of research is quasi-experimental with the research design used is Non Equivalent Control Group Design. The population in this study were 6 classes with a total of 182 students. Sampling was done by simple random sampling as many as 65 students, consisting of 33 students for the experimental class and 32 students for the control class. The instrument used is a test of physics learning outcomes as many as 30 test items. Based on the results of descriptive and inferential analysis shows that the physics learning outcomes of class X students of SMA Negeri 1 Ma'rang who take lessons using computer media through the Microsoft Power Point program obtained an average total score of 9.58. Meanwhile, for students who take part in learning using computer media through the Microsoft word program, an average total score of 8.21. The results of the inferential statistical analysis revealed that there was a significant difference between the attitudes of the students of SMA Negeri 1 Ma'rang who were taught using the Microsoft power point program and those taught with the Microsoft Word program. Thus, physics learning outcomes of students who are taught using the Microsoft power point program better than using with the Microsoft Word program.